Effect of a novel soy fermented product enriched with isoflavones and calcium on bone tissue of rats. - Bedani, Raquel; Rossi, Elizeu Antonio [UNESP]; Lepera, José Salvador [UNESP]; Wang, Charles Chenwei; de Valdez, Graciela Font (Archivos Latinoamericanos Nutricion, 2006)
The objective was to evaluate the effect of soy fermented product intake on the corporal weight and bone tissue of ovariectomized mature rats. This product was fermented with Enterococcusfaecium and Lactobacillus jugurti and enriched with isoflavones and calcium. The animals were divided in 5 groups: sham-ovariectomized; ovariectomized; ovariectomized treated with soy fermented product enriched with isoflavones and calcium; ovariectomized treated with soy fermented product enriched with calcium and ovariectomized treated with nonfermented product enriched only with calcium. In order to evaluate the effect of the tested product on bone tissue (femur and tibia), the following parameters were analyzed: length; mechanical assay of three points; density (Archimedes principle); mineral content; calcium content; measure of the trabecular widths. The corporal weight of group treated with soy fermented product containing isoflavones and calcium showed no statistical difference from sham-ovariectomized group and trabecular widths tended to have larger than ovariectomized group. However, there was no significant difference to the other evaluated parameters in result of the diverse treatments. Thus, soy fermented product enriched with isoflavones and calcium inhibited the increasing of corporal weight caused by ovariectomy and revealed a tendency to trabecular protection after castration.
Keywords: soy fermented product; isoflavones; calcium; bone tissue